Marando Bora “Better vines” - For higher sweetpotato production in the Lake Zone of Tanzania - International Potato Center (2011)
Access to timely, quality sweetpotato planting vines in the Lake Zone of Tanzania can improve food security and nutrition, especially during times of drought, crop disease, and hunger. The Marando Bora project has established and trained 27 decentralized vine multipliers (DVMs), who have distributed quality vines to 10,000 households. Working with women’s groups the project has increased women’s participation as vine multipliers to 70% and has ensured that 73% of the vine recipients were women.